VARIASI PRODUK UMKM DESA BENTENG HILIR SEBAGAI PILAR MEMBANGUN EKONOMI DESA - Dian Iriani; Diana Sari; Ratih Hardia Tiningtias; Elsa Elviana; Azat Aprianto; Riri Liardini Putri Anjani; Selvia Selvia; Nur Rizki Asih; Marzul Rahma Saputra; M. Ari Wahyudi; M. Ridho Pratama (COVIT (Community Service of Health), 2022)
Benteng Hilir Village is a fairly large village with a total area of ??15,426 hectares or equal to 154.26 km2. Benteng Hilir village is located in Mempura sub-district, Siak district, Riau province, Indonesia. This village consists of 14 Neighborhoods and Hamlets . The livelihoods of its citizens are diverse, namely: Breeders, Farmers, Entrepreneurs, Employees, Civil Servants, POLRI, Contractors, Drivers and so on. This village has a lot of potential that can be developed by the residents or the local community here. The development of the potential of this village is carried out by residents through the development of various MSME products. There are various kinds of MSME products developed by the community, namely; MSME products are cassava, kelulut honey, sugar cane juice and others. Kukerta students, Riau University, Benteng Hilir Village themselves have a role in helping MSME actors in the production process or making MSME products. The real results of these MSME activities can be seen from the opening of employment opportunities so as to reduce the number of unemployed people. This activity is carried out by students as a form of concern to the problems of rural economic development. Hopefully, with this activity, village MSMEs will continue to progress, so that they can help build the village economy. Keywords: Community Service, UMKM, Village potential